PENGARUH TUNTUTAN TUGAS TERHADAP KEPUASAN KERJA ANGGOTA DPRD KABUPATEN PASAMAN BARAT DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING - Yurasti Yurasti (Jurnal Apresiasi Ekonomi, 2016)
This study aimed toseehowthe task demandsaffectjob satisfactionandseealso whetherwork stressrole asa variableintervening. Theresults ofthis study, thevariabletask demands (X) effect significantly 0,002. However, the value ofthe variabletask demandsregression coefficienthas decreasedfrom0.409into0.272. Work stress variable(I) as an intervening variablesignificant effect onjob satisfaction(Y) with regression coefficientis0.311andsignificantlevelof0,000. The amount effect ofwork stresson job satisfaction(Y) is0.443(R2 = 4.43). In other words,an increase invariableeffectof work stresson job satisfaction(Y) by 18%orfrom2.93%to 4.43%.It can beinterpretedthat thework stress variable(I) partiallymediatethe relationshipbetweentask demandsvariables(X) to job satisfaction(Y). Keywords :Task Demands, Job Stress, Job satisfaction